Study the influence of some Listeria monocytogenes antigens on the side effects of Mitomycin C: Ibrahim Z.I.1 , Al-Wan . M. J.1 and Nahi Y. Yaseen2 - I., Ibrahim Z. (The Iraqi Journal of Veterinary Medicine, 2012)
For studying in vivo influence of immune responses on side effects of Mitomycin C (MMC),Sixty-five male-white mice were divided to nine groups ;1st group inoculated MMC,I.P,0.4mg/ml,2 doses weekly/4 weeks;2nd to 7th groups immunized S/C with LM Ags(25mg/ml) protein concentration 0.4 ml, 2doses/2 weeks intervals;2nd and 3rd groups immunized CFLMAgs and CFLMAgs-MMC in 3rd group; also 4th and fifth groups but immunized with WSLMAgs; 6th and 7th groups inoculated with 0.4 ml Attenuated LM (LaLMAgs), 7th group immunized-MMC treated. Post-immunization, 5 animals sacrificed from 1-7groups and negative control to study the cellular and humoral immunity as well as bone marrow taken to cytogenic examination ,other animals from 1-7 groups and 8th group challenged with 0.4 ml of (ViLM) containing(1x109 CFU/ml) of), the animals of negative group inoculated 0.4 ml of sterile PBS,S/C.Results; showed high mean values of IFN-y and IgG1 in animals immunized with LM.Ags, while MMC decreased levels of IFN-y and IgG1and MI%, increased chromosomal aberrations and micronucleus while decreased in immunized also immunized–MMC treatment , immunized animals show increased MI%.The suppurative pathological lesions and suppurative granulomatous lesions were appeared clear in tissue sections of internal organs in animals of positive control,decreased severity in immunized,immunized-MMCtreated especially with LaLM immunization.